The Joint Effects of Oil Price Volatility and Environmental Risks on Non-performing Loans: Evidence from Panel Data of Organization of the Petroleum Exporting Countries - Idris, Ismail Tijjani; Nayan, Sabri (EconJournals, 2016)
This paper analyses the joint effects of oil price volatility and environmental risks on non-performing loans (NPLs).Using panel data of 12 Organization of the Petroleum Exporting Countries (OPEC) for 2000-2014, we test hypotheses of joint effects of oil price changes and environmental risks on NPLs.Estimates from static panel model highlights the explanatory power of systemic risks theory in linking the effects of oil price volatility and environmental risks on NPLs and underpins their importance for policy implication purposes in OPEC member states.This calls for concerted policy and management response for assessing oil price sensitive and disaster riskiness of borrowing entities.This paper is of particular value to oil dependent countries such as OPEC member states that are net oil exporting countries.From the policy perspectives, there is need for banking regulators to consistently ensure the conduct of both micro-stress and macro-stress tests of loans against the systemic risks of oil price volatility.In addition, policymakers in the banking system should redesign their prudential guidelines to take care of the credit risks vulnerabilities associated with environmental risks and spread their risks across industries and geographical areas that are less prone to disasters.